no way dude really? thats so cool
Answer:
i think its b but im sorry if im wrong
Step-by-step explanation:
Length from R(-2, 4) to S(3, 4) is sqrt((3 - (-2))^2 + (4 - 4)^2) = sqrt(5)^2 = 5 units
Length from S(3, 4) to T(3, -1) is sqrt((3 - 3)^2 + (-1 - 4)^2) = sqrt(-5)^2 = 5 units
Therefore, total length = 5 + 5 = 10 units.
Answer:
exact form: 13 over 6
decimal form: 2.16
mixed number form: 2/ 1 over 6
Answer:
ab² - 9
Step-by-step explanation:
Given in the question an expression
(ab + 3)(ab - 3)
To product mentally we will use polynomial identity called
Difference of squares
<h3>a² - b² = (a+b)(a-b) </h3>
here a = ab
b = 3
(ab + 3)(ab - 3) = ab² - 3² = ab² - 9